(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to set phrases and their components in the form of a sentence, it talks about the properties of words and set phrases, which are the building material of a sentence. At the same time, he commented on the interpretation of a set phrase, focused on defining the functional border between a phrase and a sentence. The researcher justified his conclusions based on the analysis of the examples presented in the article.